2018
DOI: 10.1002/pc.25117
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(sodium acrylate/cement clinker) DN hydrogel composites

Abstract: A series of poly(sodium acrylate)/(cement clinker) [P(NaA-AA)/CC] double network (DN) hydrogel composites were prepared by solution polymerization at room temperature, using partially neutralized acrylic acid (NaA-AA) as an organic precursor and cement clinker (CC) as an inorganic precursor, redox system of potassium persulfate/sodium bisulfite (KPS/SHS) as initiator and sorbitol (Sbt) as cross-linking agent. The polymerization of organics and the hydration of inorganic substances were reflected in the tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In recent years, some promising polymer hydrogels have been intensively investigated in view of their potential application to articular cartilage defects and their repair. Shi et al found that the addition of acrylamide (AAm) significantly improved the friction behavior of poly­(vinyl alcohol) (PVA) hydrogel. The COF for PVA/PAAm DN hydrogels fluctuates from 0.2 to 0.02 at lower loads, and this phenomenon is attributed to the biphasic lubrication mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some promising polymer hydrogels have been intensively investigated in view of their potential application to articular cartilage defects and their repair. Shi et al found that the addition of acrylamide (AAm) significantly improved the friction behavior of poly­(vinyl alcohol) (PVA) hydrogel. The COF for PVA/PAAm DN hydrogels fluctuates from 0.2 to 0.02 at lower loads, and this phenomenon is attributed to the biphasic lubrication mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…The significantly improved water retention ability could be ascribed to the increased specific surface area and waterlocking capacity after HA mineralization. 59 High porosity and interconnected pore structure are desirable for bone tissue engineering scaffolds, which are conducive to migration and proliferation of osteoblasts and mesenchymal cells, angiogenesis and transport of nutrients and metabolites, thus increasing the bone formation ability of the materials. 60 The porosity/pore size of PBLG microcarriers before and after surface carboxylation were 92.2 ± 5.7%/47.1 ± 1.9 μm and 93.2 ± 5.1%/48.0 ± 1.6 μm, respectively (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…However, water retention of cluster HA/PBLG and acicular HA/PBLG microcarriers reached 569 ± 25 and 686 ± 29%. The significantly improved water retention ability could be ascribed to the increased specific surface area and water-locking capacity after HA mineralization …”
Section: Resultsmentioning
confidence: 99%
“…3C and D are in agreement with the literature. 40,46 Comparing to PC/PAM composites, cement paste had a higher strength (about 1320 kPa) but a poorer ductility at 3 days age. Among these PC/PAM composites, PC120/PAM8 had the highest tensile strength of 1200 kPa and an elongation of 100%, while for PC60/PAM8, the strength and elongation were 156 kPa and 740% and for PC30/PAM8, they were 70 kPa and 800%.…”
Section: Mechanical Properties Of Pc/pam Compositesmentioning
confidence: 99%
“…For PC/PAM composites, the inorganic particles can serve as crosslinker and a more rigid wall structure was built up. 40,46 The pore size has been reported to be essential for the adsorption efficiency of ions. 47 Also, pore diffusion is one of the common adsorption mechanisms to remove contaminants in water.…”
Section: Microscopic Characterizationmentioning
confidence: 99%